KONSEP CAKRA YADNYA TERHADAP PENGGUNAAN BUAH IMPORT DI BALI (Studi Kasus Perayaan Hari Raya Galungan) - Putu Maria Ratih Anggraini (Jnanasidanta, 2019)
The belief of the Hindu community towards God the Almighty is practiced through the Religious Ceremony with the actual practice of being Banten/Upakara which is something that is no longer a special thing for Hindus in Bali. In making the ceremony the Hindus began to use the means imported from abroad, this was due to the desire of the people to use better, more interesting, tasty fruit to eat. In the process of making this pillow, the people who performed the Chakra Yadnya Concept did not feel it was a concept of Hindus who contributed to the economy in the community (or in other words contributed to the economic turnover of the community). In the use of local fruits in Beryad, especially on Galungan holidays, more facilities are needed, more people will benefit, including imported fruit previously translated into Hindu language that has proven beneficial to the world that has used fruit from the outside world to Yadnya. Keyword : cakra yadnya, buah import